Pengaruh Good Corporate Governance Dan Kompetensi Sumber Daya Manusia Terhadap Kualitas Laporan Keuangan - Naiaki, Maria Fridolina; Kadir, Kadir; Limarjani, Sustinah (Politeknik Negeri Ambon, 2024)
This study aims to test and re-analyze previous researchers between independent variables, namely the variables of transparency, accountability, responsibility, independence, fairness and competence of human resources on the quality of financial reports of Private hospitals in the city of Balnjalrmalsin. The type of data in this study is primarily dental, namely questionnaires distributed to employees of private hospitals in the city of Balnjalrmalsin. The subjects in this study were the director, deputy director, head of finance, and employees of the finance department, totaling 62 people. The method of data analysis was carried out using the multiple linear regression method with the calculation process using the SPSS 22 application program. The results of the study show that transparency, accountability, and human resource competence have significant effects on the quality of financial reports. Responsibility and independence have no effect on the quality of financial reports. Fairness has a negative effect on the quality of financial reports.